Enhancing Customer Satisfaction Through Upselling and Cross-Selling: The Mediating Role of Brand Image in Automotive After-Sales Services - Doniartha, I Made Leo; Indiani, Ni Luh Putu; Setini, Made; Putra, Ida Bagus Udaya (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
After-sales service is an important aspect in building long-term relationships with customers and increasing customer satisfaction with a brand. The implementation of sales strategies such as upselling and cross-selling in after-sales service aims to increase transaction value and shape positive customer perceptions of the brand. Therefore, this study aims to analyze the effect of upselling and cross-selling on customer satisfaction with brand image as a mediating variable in Toyota Tabanan after-sales service. The population in this study were all customers who use Toyota Tabanan after-sales service. The research sample consisted of 100 respondents selected using a purposive sampling technique. The data collection method was carried out through distributing questionnaires. The analysis technique used to test the hypothesis was inferential analysis using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results showed that upselling and cross-selling had a positive effect on customer satisfaction and brand image. Brand image also had a positive effect on customer satisfaction and was able to mediate the effect of upselling and cross-selling on customer satisfaction. These results indicate that implementing the right sales strategy and strengthening brand image in after-sales service can increase customer satisfaction sustainably.